CONTEXTUALIZAÇÃO HISTÓRICA DA FORMAÇÃO DO PROFESSOR PARA AS SÉRIES INICIAIS DO ENSINO FUNDAMENTAL - Luciana Scarcelli Moré Oliveira; Raimunda Abou Gebran; Tereza de Jesus Ferreira Scheide (Universidade do Oeste Paulista, 2008)
This work is part of a research undertaken with schools and teachers in the initial grades of elementary school. One of the fundamental objectives is to understand how it is setting the process of training these professionals. To further examine, the training of teachers in Brazil there was a need to present a brief historical context so you can understand how professionally developed this career. To serve in both a literature review, consider looking at different moments in the history of Brazilian education stood as the process of training of teachers from the initial series, considering the educational policies and legislation proposed for the training of teachers of this level of education. Also, we present and discuss the existing laws that guide the teacher training today. This review on the training of the teacher shows how fragmented and discontinuous process that has been over the decades and how this training policy is reflected in the Brazilian educational system. If we decrease the rates of school dropout and repetition, to seek recovery of the quality of learning and consequently the improvement of education and training Brazilian critical and effective participation of citizens, there must be a concern with the formation of the main responsible for this whole process : the teacher.The joint effort between the public educational policy-makers, the investment in initial and continuing training of teachers, the dialogue between school and university are proposed to improve basic education.